La Universidad Virtual del ITESM: hacia una transformación de la educación superior - Marisa MARTÍN (Ediciones Universidad de Salamanca, 2016)
This article presents a virtual space for education developed at the Instituto Tecnológico y de Estudios Superiores de Monterrey (ITESM) in Mexico. It describes problems and achievements, educational and technological decisions that have been made, the implications at an organizational level and of the actual protagonists of the process: teachers and students, trends and issues. The ITESM Virtual University is becoming a dynamic institution in a continual process of construction and evolution, an institution that has incorporated innovation and creativity into its working philosophy, that is permanently adapting the new technologies to educational processes, and is open to national and international educational needs while presenting different options for giving an educational response of quality in future years.